A nyelvtörvények és nyelvhasználat tisztázatlan kérdései a XIX. századi Magyarországon : asszimiláltunk, vagy segítettük a kulturális önállósodást? - Bácsfainé Hévizi, Józsa (Közép-Európai Közlemények, 2010)
The variety of the regional autonomy in Hungarian Kingdom exists from the 12–13thcentury. The self-government with different administrative system of Székelys (a kind of Magyar troops of Eastern Transylvania), Saxons, Cumans, Jazygians and Croatia gave possibility to practice collective rights and preserve their language, identity until the 19th century. With the exeption of Saxons the nationality groups described were given their privileges in return for military service. (Similary development is visible in Switzerland.) The Ecclesiastic Autonomy for the Romanian, Serbian, and Ruthenian immigrants, who came into Hungary from the 15th century continuosly, granted the use of mother language in schools and churches, maintained by their foundations and the government. The king’s edicts were reinforced by Actsof 1791–1792. The Transylvanian princes of 16–17thcenturies prescribed that the language used in the Romanian churches be changed from the previous liturgical Slavic to contemporary Romanian, and opened the first schools, press for them on Romanian. In the 13thcentury, the newcomer german (saxon) population having hospes-rigths in Hungary formed the specific town-communities: The imperial manifestos guaranteed the use of own administration on their native language. The members of the board senate and thelocal council had to be elected by the rate of nationalities, living in the town, and by the rates of religious sects. In addition to officially 3-4 native language speaking towns like Pozsony (Bratislava), Buda, Pécs, Kassa (Kosice), Baja, Zágráb (Zágreb), Zsolna (Zilina), Kolozsvár (Cluj), Kassa (Kosice), were some towns where temporary the administrative language weren’t Hungarian; like Baja of the 17thcen-tury, and the german town Gyula of the 18thcentury. The town-council frequently had minority-councils of ationalities, like Serb town-council of Buda, Jewish town-council of Baja, Gipsy town-council of Siklós in the 18th century. The legal continuity are effective in the Act IX of 1868, which guarantee the Romanian and Serbian orthodox churches with cultural autonomy, Act XLIV of 1868 guaranted the minority language could be used in official documents, administrative matters wherever 1/5 of the representatives of the municipality demanded it.